Statistical Yearbook 2008, Fifty-third Issue - United Nations Department of Economic; Social Affairs (United Nations, 2011)
The Statistical Yearbook is an annual compilation of a wide range of international economic, social and environmental statistics on over 200 countries and areas, compiled from sources including UN agencies and other international, national and specialized organizations. The 53rd issue contains data available to the Statistics Division as of 31 October 2009 and presents them in over 70 tables on topics such as: agriculture, forestry and fishing; balance of payments; communication; development assistance; education; energy; environment; finance; gender; industrial production; international merchandise trade; international tourism; labour force; manufacturing; national accounts; population; science and technology; transport; and wages and prices. The number of years of data shown in the tables varies from one to ten, with most tables covering 1996 to 2008. Accompanying the tables are brief descriptions of major statistical concepts.